Factors Affecting on Clinical Practice Performance among Undergraduate Nursing Students - Mohite, Namarta C; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT: Nursing education prepares the students from various societies and convictions to be able in rendering professional nursing care to people of all ages, in all stages of health and illness. Nursing students are required to acquire and learn relevant skills and knowledge in the medical, behavioral and biological sciences. The present study planned for distinguishing the variables influencing clinical practice among undergraduate nursing students. METHODS -A cross-sectional research design was used to conduct the study. The study included sampling of 275nursing students at Krishna institute of medical sciences deemed to be university. Self-administered questionnaires were utilized as a tool. Data was collected over a time of 3 months. The data were coded. Analysis was done by SPSS software version 20 for windows. Results- A total of 275 undergraduate nursing students majority were 234 (85.09%) while male were 41 (14.90%). The most detailed factor that improved clinical practice was successful supervision and evaluation as reported by 42.3% of members. The reported barriers incorporate students factors such as, absence of self-assurance and non-appearance, college factors for example inappropriate supervision and poor planning of clinical teachers. Anxiety among the undergraduate nursing students was identified with dread of committing errors (47.9%) and absence of competency (31.2%). There was significant association between Barriers of Effective Clinical Practice and Gender, Age. We found a huge relationship between barrier and gender .More male nursing students (62.1%) essentially revealed unsupportive environment as a barrier than female (35.6%). Similarly, period of members didn’t have significant association with successful clinical practice. Deficiency of staff in the hospital influenced clinical supervision as reported by 89.6% of the students. Majority of nursing students (84.4%) agreed that parent’s monetary status influenced clinical practice. Absence of cash made failure bear the cost of learning materials and other individual needs. Conclusion - Deficient supervision by clinical educators, absence of resources, quality of practical appraisal in clinical region, and anxiety were a portion of the elements that barriers for successful clinical learning. Student’s readinesses, competency of the clinical of teacher, and perspectives of staff towards students in clinical area have significance performance in clinical practice. Contemplating these outcomes, we propose offering preclinical orientation to the students and conveying and explaining clinical learning objectives to Students before reporting to clinical.